Thermally Powered Soft Gripper Covered with Silver Coated Nylon Fabric Heater Reinforced with Stainless Steel Yarn - ÇELEBİ, MEHMET FATİH (My University, 2024)
Soft grippers, generating movement immediately, are generally based on flexible materials actuated by air pressure and comprised of bulky parts, including valves, compressors/pumps, motors, and tubes. In this work, a compact soft gripper with the ability to actuate with a low boiling point liquid (acetone) is presented. SolidWorks 2021 software and 3D printing technology are used to design and manufacture the gripper molds, respectively. The constitutive material of the soft gripper body is highly flexible Ecoflex. A silver-coated nylon fabric (SCNF) heater reinforced with stainless steel yarn (SSY) covering the external surface of the gripper was designed and manufactured using Autocad 2021 and a laser cutting machine, respectively. The idea is inspired by floating the gripper in warm water to provide smooth heat over a large surface area. The available commercial software Abaqus2021 is used to simulate the mechanical deformation of the gripper, and its results are verified with experimental results. The parameter’s effect including the voltage and low boiling liquid volume on achievable force and actuating time are investigated. The relation between the electrical, thermal, and mechanical properties of the presented gripper is discussed in detail.
Keywords: Makina Mühendisliği; Makina Teorisi ve Dinamiği; Robotik; Mekanik; Sonlu Elemanlar Yöntemi; Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Mechanical Engineering; Machine Theory and Dynamics; Robotics; Mechanical; Finite Element Methods; Textile Engineering and Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, TEXTILES; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Fizik Bilimleri; Computational Mechanics; Automotive Engineering; Physical Sciences